Raman spectroscopy of supported lipid bilayers and membrane proteins - Lee, C; Lee, Chongsoo (2005)
﻿ Off-resonance unenhanced total internal reflection (TIR) Raman Spectroscopy was explored to investigate supported single lipid bilayers with incorporated membrane peptides/proteins at water/solid interface. A model membrane was formed on a planar supported lipid layer (pslb) by the fusion of the reconstituted small unilamellar vesicles (SUVs), and the intensity of bilayer was confirmed by a comparison of Raman spectral intensity in the C-H stretching modes with C16TAB. With prominent Raman sensitivity attained, we studied the 2-D phase transition of DMPC and DPPC pslbs and the temperature-dependent polarised spectra revealed a broad transition range of ca. 10 °C commencing at the calorimetric phase transition temperature. We applied polarised TIR-Raman Spectroscopy to pslbs formed by DMPC SUVs reconstituted with a model membrane-spanning peptide gramicidin D. A preferential channel structure formed by dissolution of trifluoroethanol could be probed by polarised Raman Spectroscopy qualitatively showing an antiparallel β-sheet conformation (different from "standard" one) and our Raman spectra by correlation with NMR and CD data confirmed single-stranded π6.3 β-helical channel structure in the single bilayer. We also studied the membrane-penetrating peptide indolicidin in the presence of DMPC pslb over the chain melting temperature and a β-turn structure was dominantly observed concomitant with membrane perturbation. Dynamic adsorption of DPPC to form pslb from a micellar solution of n-dodecyl-β- D-maltoside could be examined with high sensitivity of every 1-min acquisition. Finally we used polarised TIR-Raman scattering to porcine pancreatic phospholipase A2 hydrolytic activity on DPPC pslbs and revealed lipid-active conformation different from that of the enzyme alone.